Variability of pgm‑Region Genes in Yersinia pestis Strains from the Caspian Sandy and Adjacent Plague Foci - P. A. Goryunova; G. A. Eroshenko; L. M. Kukleva; E. A. Naryshkina; Z. L. Devdariani; N. S. Chervyakova; V. V. Kutyrev (Проблемы особо опасных инфекций, 2023)
The aim of the study was to compare the nucleotide sequences of pgm‑region genes in Yersinia pestis strains isolated on the territory of the Caspian sandy and adjacent plague foci in 1925–2015. Materials and methods. 65 Y. pestis strains from the Caspian sandy and adjacent plague foci were used in the work. DNA isolation was performed using the PureLink Genomic DNA Mini Kit. Whole genome sequencing was conducted in Ion S5 XL System (Thermo Fischer Scientific). Data processing was carried out using Ion Torrent Suite software package 3.4.2 and NewblerGS Assembler 2.6. To compare the obtained sequences with the NCBI GenBank database, the Blast algorithm was used. The phylogenetic analysis was performed according to the data of whole genome SNP analysis based on 1183 identified SNPs. The search for marker SNPs was performed using the Snippy 4.6 program. The phylogenetic tree was constructed using the Maximum Likelihood algorithm, the GTR nucleotide substitution model. Results and discussion. The nucleotide sequences of pgm‑region genes of 65 Y. pestis strains from the Caspian sandy and adjacent plague foci have been assessed. Single nucleotide substitutions have been identified in Y. pestis strains from the Caspian sandy and Kobystan plain-foothill foci in the hmsR, astB, ybtS, ypo1944, ypo1943, ypo1936 genes, as well as a deletion of 5 bp in the ypo1945 gene, which is characteristic of strains of one of the phylogenetic lines of Y. pestis from the foci of Caucasus and Transcaucasia, isolated in 1968–2001. The data obtained can be used to differentiate Y. pestis strains from the Caspian sandy focus, as well as to establish the directions of microevolution of the plague pathogen in this region and adjacent foci.